Perpustakaan digital: peranan repositori institusi Universiti Sains Malaysia - Hashim, Siti Fatimah; Wan Jan, Noor Azlinda; Mohamad Shahini, Meor Mohd Arafat (Persatuan Pustakawan Malaysia, 2013)
The Universiti Sains Malaysia Institutional Repository (Repository@USM) serves as a repository for storing a variety of electronic information materials such as articles from academic magazines, books, thesis, examination papers, research reports, photographs and others. This repository provides free access to the world and can be used freely for research and learning at the University. It can be used as an online reference source that is easy, effective and accessible at any times via the Internet. This repository also plays a role to guarantee continuity of intellectual property in the USM community as an online reference source and supports the vision and mission of USM Library in order to achieve the APEX standard. The establishment of the library’s institutional repository has helped transform the Library into a digital library where materials can be accessed quickly through a computer network anytime anywhere in line with current fast growing technological developments.